Taxonomic status and morphological variation of Hydrodynastes bicinctus (Hermann, 1804) (Serpentes: Dipsadidae) - Murta-Fonseca, Roberta A.; Franco, Francisco L.; Fernandes, Daniel Silva (Zootaxa, 2016)
Hydrodynastes bicinctus was described with no type material or locality and it has two subspecies currently recognized that are not taxonomically well defined. We tested the validity of the two subspecies through meristic, morphometric, and color pattern characters. Two apparently distinct color patterns of H. bicinctus were noticed, one from the Cerrado open formations and the other from the Amazon rainforest. These aforementioned patterns, however, exhibited a high degree of geographic overlap and many specimens showed a blended pattern. Based on these results we propose synonymizing H. bicinctus schultzi with the nominal taxon. Furthermore, we designate a neotype for the species, present data on geographic distribution, and provide morphological descriptions of the hemipenis, cephalic glands, and skull.